2016
DOI: 10.1177/1062860615594879
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Return Visits Resulting in Admission

Abstract: Prior studies have suggested that emergency department (ED) return visits resulting in admission may be a more robust quality indicator than all 72-hour returns. The objective was to evaluate factors that contribute to admission within 72 hours of ED discharge. Each return visit resulting in admission was independently reviewed by 3 physicians. Analysis was by descriptive statistics. Of 45 071 ED discharges, 4.1% returned within 72 hours; 0.96% returned for related reasons and were admitted to wards (91.2%), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…These may include multidisciplinary assessment areas or wards, or enhanced geriatric outreach services that aim to prevent unplanned hospital readmissions. Jelinek et al 6 in a study of adult frequent attendees in Perth showed that moderately frequent attendees (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) presentations per year) were more urgent compared with the 'average' ED patient. This was consistent with the findings of the present study and supported by the higher admission rate observed in this group of patients but also reflects the observation that the age specific rates of frequent representations were still highest in the elderly (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These may include multidisciplinary assessment areas or wards, or enhanced geriatric outreach services that aim to prevent unplanned hospital readmissions. Jelinek et al 6 in a study of adult frequent attendees in Perth showed that moderately frequent attendees (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) presentations per year) were more urgent compared with the 'average' ED patient. This was consistent with the findings of the present study and supported by the higher admission rate observed in this group of patients but also reflects the observation that the age specific rates of frequent representations were still highest in the elderly (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These observations in conjunction with the lower in-patient admission rate in this group suggested that improved community case management in areas of mental health and drug and alcohol services as well as including primary care coordination and education 14 may help to prevent unplanned ambulance use and representations to ED and supports the need for improved continuity and access to care for those with mental illness. 15,16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the proportion of return visits arising from quality-of-care problems in the index visit, sometimes termed ‘avoidable causes’, ‘preventable adverse events’ or ‘adverse events related to ED care’, the very few studies to address this question estimate that it affects 3%–11% of returns 8 18 and 5%–21% of the cases resulting in admission 2 7 12 15 18. Several studies have described an increased frequency of quality-of-care problems among patients who were hospitalised after the return visit,2 8 18 although in another study no such relationship was detected 7…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have used other time limits,1 3 4 8 10 12–14 have stipulated that the return visit must involve the admission of the patient7 12 15 16 or have limited their analysis to return visits presenting the same diagnosis 10. Therefore, a review of the literature concluded that it is necessary to investigate which unscheduled return visits are associated with quality issues 17…”
Section: Introductionmentioning
confidence: 99%